1995
DOI: 10.1246/bcsj.68.123
|View full text |Cite
|
Sign up to set email alerts
|

The Dependence of the Polarity of Solvents on 1,3 : 2,4-Di-O-benzylidene-d-sorbitol Gel

Abstract: 1,3 : 2,4-Di-O-benzylidene-d-sorbitol (d-DBS) is known as a chiral oil gelator for a wide variety of organic solvents. The relationship between texture, structure of the gel, and the aggregated structure formed by d-DBS was investigated in various solvents. In the low polar solvents, the gel held a mesh type network structure in which the fiber appeared to be a rope-like helical structure. In the moderately polar solvents, the gel held an isotropic mesophase, but in the polar solvents, a spherulite texture was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 8 publications
4
41
0
Order By: Relevance
“…36 For the alternative energy-minimized conformations of DBS, it was found that p-p interactions (between phenyl groups in the equatorial position) were also present, in some agreement with the results of Watase. With respect to intermolecular interactions, they found that for the initial energy-minimized configuration of DBS, the only interaction in the dimer was the formation of a hydrogen bond between the 6-OH group of one DBS molecule and an acetal oxygen of the other -in agreement with the model proposed by Yamasaki.…”
Section: Experimental and Computational Conceptssupporting
confidence: 75%
See 2 more Smart Citations
“…36 For the alternative energy-minimized conformations of DBS, it was found that p-p interactions (between phenyl groups in the equatorial position) were also present, in some agreement with the results of Watase. With respect to intermolecular interactions, they found that for the initial energy-minimized configuration of DBS, the only interaction in the dimer was the formation of a hydrogen bond between the 6-OH group of one DBS molecule and an acetal oxygen of the other -in agreement with the model proposed by Yamasaki.…”
Section: Experimental and Computational Conceptssupporting
confidence: 75%
“…36 They reacted L-glucono-1,5-lactone with two equivalents of benzaldehyde dimethyl acetal to first yield the intermediate 3,5:4,6-dibenzylidene-L-gluconic acid. Yamasaki and co-workers reported an interesting alternative approach to the 5-methoxy derivative of DBS based on the use of different starting materials.…”
Section: Dbs and Its Derivatives: A Chronicle Of Synthetic Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The supramolecular self-assembly of DBS has been extensively investigated. A common conclusion is that DBS is capable of self-assembly into a 3D nanofiber network [26][27][28]. We observed that DBS nanofibers and PANI-PSS chains entangle each other, leading to the formation of dual interpenetrated networks and thereby reinforcing the hydrogels.…”
Section: Introductionmentioning
confidence: 82%
“…2,3 It is known to cause gelation in the semidilute concentration range ͑Ӷ5%͒ in a great variety of liquids ranging from chloroform 4 to ethylene glycol 5 and siloxanes. 6 Gel formation in these solvents is attributed to an association of DBS molecules into well-ordered helical aggregates 2 that interwind to form a submicron scale three-dimensional network, turning the solutions into viscoelastic solids.…”
Section: Introductionmentioning
confidence: 99%